أثر تقلبات سعر الصرف على الميزان التجاري الجزائري دراسة قياسية (1990-2017) - بن رجم محمد خميسي; بومدين وفاء (My University, 2019)
تهدف هذه الدراسة إلى قياس أثر تقلبات سعر صرف الدينار الجزائري مقابل الدولار الأمريكي على الميزان التجاري خلال الفترة من 1990 إلى 2017، مع إظهار مختلف المراحل التي مر بها سعر الصرف في الجزائر، وتم قياس أثر التقلبات باستخدام نموذج الانحدار الذاتي ذو الإبطاء الموزع ARDL. توصلت الدراسة إلى وجود علاقة عكسية بين سعر الصرف والميزان التجاري الجزائري في الأجلين القصير والطويل. This study aims at measuring the impact of the fluctuations of the Algerian dinar exchange rate against the US dollar on the trade balance during the period from 1990 to 2017 , showing the different stages that passed by the exchange rate in Algeria. the effect of fluctuations was measured using Autoregressive-Distributed Lag Model ARDL.The study indicates an inverse relationship between the exchange rate and the Algerian trade balance in the short and long term.